Examining the Type, Quality, and Content of Web-Based Information for People With Chronic Pain Interested in Spinal Cord Stimulation: Social Listening Study - Maarten Moens; Leen Van Doorslaer; Maxime Billot; Edgard Eeckman; Manuel Roulaud; Philippe Rigoard; Maaike Fobelets; Lisa Goudman (JMIR Publications, 2024)
BackgroundThe increased availability of web-based medical information has encouraged patients with chronic pain to seek health care information from multiple sources, such as consultation with health care providers combined with web-based information. The type and quality of information that is available on the web is very heterogeneous, in terms of content, reliability, and trustworthiness. To date, no studies have evaluated what information is available about neuromodulation on the web for patients with chronic pain. ObjectiveThis study aims to explore the type, quality, and content of web-based information regarding spinal cord stimulation (SCS) for chronic pain that is freely available and targeted at health care consumers. MethodsThe social listening tool Awario was used to search Facebook (Meta Platforms, Inc), Twitter (Twitter, Inc), YouTube (Google LLC), Instagram (Meta Platforms, Inc), blogs, and the web for suitable hits with "pain" and "neuromodulation" as keywords. Quality appraisal of the extracted information was performed using the DISCERN instrument. A thematic analysis through inductive coding was conducted. ResultsThe initial search identified 2174 entries, of which 630 (28.98%) entries were eventually withheld, which could be categorized as web pages, including news and blogs (114/630, 18.1%); Reddit (Reddit, Inc) posts (32/630, 5.1%); Vimeo (Vimeo, Inc) hits (38/630, 6%); or YouTube (Google LLC) hits (446/630, 70.8%). Most posts originated in the United States (519/630, 82.4%). Regarding the content of information, 66.2% (383/579) of the entries discussed (fully discussed or partially discussed) how SCS works. In total, 55.6% (322/579) of the entries did not elaborate on the fact that there may be >1 potential treatment choice and 47.7% (276/579) did not discuss the influence of SCS on the overall quality of life. The inductive coding revealed 4 main themes. The first theme of pain and the burden of pain (1274/8886, 14.34% coding references) explained about pain, pain management, individual impact of pain, and patient experiences. The second theme included neuromodulation as a treatment approach (3258/8886, 36.66% coding references), incorporating the background on neuromodulation, patient-centered care, SCS therapy, and risks. Third, several device-related aspects (1722/8886, 19.38% coding references) were presented. As a final theme, patient benefits and testimonials of treatment with SCS (2632/8886, 29.62% coding references) were revealed with subthemes regarding patient benefits, eligibility, and testimonials and expectations. ConclusionsHealth care consumers have access to web-based information about SCS, where details about the surgical procedures, the type of material, working mechanisms, risks, patient expectations, testimonials, and the potential benefits of this therapy are discussed. The reliability, trustworthiness, and correctness of web-based sources should be carefully considered before automatically relying on the content.